Structural properties, elastic anisotropies and thermal conductivities of tetragonal LnB2C2 (Ln = Rare Earth) compounds from first-principles calculations. Issue 2 (1st February 2019) - Bao, Weizong; Liu, Dan; Li, Ping; Duan, Yonghua
Abstract: In this work, we used the first-principles calculations to study structural properties, elastic constants and moduli, polycrystalline elastic moduli, anisotropic properties and thermal conductivities of tetragonal LnB2 C2 (Ln = Rare Earth) compounds. The polycrystalline elastic modulus, Poisson's ratio, hardness and Debye temperature were calculated based on the single crystal elastic constant. Estimation of elastic anisotropy was carried out by elastic anisotropy index and surface projection. The elastic anisotropy for these compounds is a sequence of LuB2 C2 > TmB2 C2 > ErB2 C2 > LaB2 C2 > HoB2 C2 > TbB2 C2 > DyB2 C2 > NdB2 C2 > PrB2 C2 > CeB2 C2 . The calculated minimum thermal conductivity and Debye temperature are in the same order of LaB2 C2 > TmB2 C2 > LuB2 C2 > ErB2 C2 > HoB2 C2 > CeB2 C2 > DyB2 C2 > NdB2 C2 > PrB2 C2 > TbB2 C2 . The obtained sound velocities and minimum thermal conductivity of LnB2 C2 compounds are also anisotropic.